1975
DOI: 10.1203/00006450-197506000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Increased Pulmonary Blood Flow on the Pulmonary Vascular Bed in Pigs

Abstract: ExtractIncreased pulmonary blood flow was produced in 1-month-old piglets by means of left pneumonectomy, arteriovenous fistulas in the neck, and a combination of both. Physiologic and histologic studies of the pulmonary vascular bed were done 1-9 months after operation.A progressive, moderate increase in pulmonary artery ( P A ) pressure was observed, especially between 1 and 6 months after surgery. This was flow related, 1.e.. the group with the highest flow (pneumonectomy plus fistula) was found to have the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…Increased flow to the right lung has been created experimentally in animals by ligating the left pulmonary artery (Leibow et al, 1950;McGrady et al, 1968;Linde et al, 1970;Rosencrantz et al, 1973;Lansimies, 1975;Haworth et al, 1981) or by banding it (Liebow et al, 1950;Cheung, 1976) or by performing a left pneumonectomy (Rudolph et al, 1961;Kato et al, 1971;Freidli et al, 1975). Banding rather than ligating the pulmonary artery avoids the increase in collateral flow associated with the latter procedure (Leibow et al, 1950).…”
Section: Increased Pulmonary Blood Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased flow to the right lung has been created experimentally in animals by ligating the left pulmonary artery (Leibow et al, 1950;McGrady et al, 1968;Linde et al, 1970;Rosencrantz et al, 1973;Lansimies, 1975;Haworth et al, 1981) or by banding it (Liebow et al, 1950;Cheung, 1976) or by performing a left pneumonectomy (Rudolph et al, 1961;Kato et al, 1971;Freidli et al, 1975). Banding rather than ligating the pulmonary artery avoids the increase in collateral flow associated with the latter procedure (Leibow et al, 1950).…”
Section: Increased Pulmonary Blood Flowmentioning
confidence: 99%
“…The series of experiments we report here is unique in that we document the differences in pressures and flows in the two lungs and relate the altered hemodynamic states to a quantitative assessment of the structural remodeling of the Hypoxia TT TT --I I TT Tf TT TT U 11 --Band + Hypoxia TT TT T -T -TTT T TTT T 11 II - Not all species demonstrate a rise in pulmonary artery pressure in response to a chronic increase in flow which we documented in this study in adult rats. For example, after left pneumonectomy, beagle puppies do not show the rise in right pulmonary artery pressure (Freidli et al, 1975) which can be demonstrated in mongrel puppies (Rudolph et al, 1961), in minipigs (Kato et al, 1971), and in piglets (Haworth et al, 1981). The latter study was the first to document that high flow to the right lung is not immediately accompanied by an increase in pressure, but only after the development of structural changes in the peripheral pulmonary arteries.…”
Section: Increased Pulmonary Blood Flowmentioning
confidence: 99%
“…Reductions in vessel wall-to-lumen ratios have been demonstrated in animal prepara tions with High blood flow [4,14]. Further more, pulmonary vessels with a low wall-tolumen ratio require greater smooth muscle contraction or a greater contractile stimulus to produce a similar change in vascular re sistance.…”
Section: Discussionmentioning
confidence: 99%
“…Left pulmonary artery ligation in dogs has been shown to increase right lung perfusion and increase pulmonary vascular respon siveness to anesthetic agents [10]. However, no change in the pulmonary pressor re sponse to hypoxia was observed after left pneumonectomy in pigs [4,9] and dogs [9], On the other hand, a decrease in pulmonary vascular responsiveness to prostaglandin F2" (PGF2o) and hypoxia has been demon strated in dogs after unilateral pulmonary artery ligation [16]. In all of these studies, however, the ability to make multiple ad justments of blood flow was limited.…”
Section: Introductionmentioning
confidence: 92%
“…[101][102][103][104] Likewise, in multiple experimental models of increased pulmonary blood flow with or without increased PAP, small PAs are usually of normal or reduced diameter. [105][106][107] Whether smooth muscle mass is normal or increased cannot be determined from the data presented, but reduced vessel diameter (and thickened media) is consistent with eutropic remodeling. Although such remodeling would not directly account for dilation lesions (which are not seen with PVH-PH but are seen with other forms of PH), increased PAP due to narrowed resistance vessels could lead to other microarchitectural abnormalities.…”
Section: Myogenic Vasoconstrictionmentioning
confidence: 99%